Implications of fiscal and financial policies for unlocking green finance and green investment - Dina Azhgaliyeva; Zhanna Kapsaplyamova; Linda Low (Asian Development Bank Institute (ADBI), 2018)
Scaling up private investment in renewable energy is indispensable for achieving decarbonization of the global economy, low carbon transformation, and climate-resilient growth. As advocated by the United Nations, governments should create a level playing field for private investment in renewable energy, and they should use fiscal policies to incentivize engagement from the private sector. While studies on renewable energy are abundant and focus on topics ranging from unlocking renewable energy investment to the effects of environmental policies on innovation, energy efficiency policies, investment policies in renewable energy, and the adoption of feed-in tariffs, studies that uncover the determinants of private investment in the renewable energy sector are limited. Unlike the previous literature, which concentrates on the total green investment, this study distinguishes between private sector investment and government investment in renewable energy. Using multilevel data from 13 countries over the period 2004-2016, this chapter investigates the impact of 4 fiscal and financial policy instruments, namely (i) feed-in tariffs, (ii) taxes, (iii) loans, and (iv) grants and subsidies, on private investment in renewable energy. A multilevel random-intercept and random-coefficient model provides evidence of the effectiveness of two policy instruments, feed-in tariffs and loans. This study could benefit policy makers and researchers by enhancing their understanding of the factors enabling the scaling up of renewable energy investment.
Keywords: Q58; Q42; H30; 330; Private investment; Feed-in tariff; Fiscal policy; Green investment; Government investment; Renewable energy